1999
DOI: 10.1523/jneurosci.19-21-09497.1999
|View full text |Cite
|
Sign up to set email alerts
|

Replay and Time Compression of Recurring Spike Sequences in the Hippocampus

Abstract: Information in neuronal networks may be represented by the spatiotemporal patterns of spikes. Here we examined the temporal coordination of pyramidal cell spikes in the rat hippocampus during slow-wave sleep. In addition, rats were trained to run in a defined position in space (running wheel) to activate a selected group of pyramidal cells. A template-matching method and a joint probability map method were used for sequence search. Repeating spike sequences in excess of chance occurrence were examined by compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

34
645
2
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 796 publications
(683 citation statements)
references
References 58 publications
34
645
2
2
Order By: Relevance
“…These processes would thus promote dynamic plastic changes in neuronal populations previously engaged in memory acquisition (Maquet, 2001). Consistently with this hypothesis, several animal studies have shown that neural activity expressed during waking behavior is reinstated during subsequent sleep (e.g., Wilson and McNaughton, 1994;Skaggs and McNaughton, 1996;Qin et al, 1997;Nadasdy et al, 1999;Louie and Wilson, 2001). …”
Section: Introductionmentioning
confidence: 62%
“…These processes would thus promote dynamic plastic changes in neuronal populations previously engaged in memory acquisition (Maquet, 2001). Consistently with this hypothesis, several animal studies have shown that neural activity expressed during waking behavior is reinstated during subsequent sleep (e.g., Wilson and McNaughton, 1994;Skaggs and McNaughton, 1996;Qin et al, 1997;Nadasdy et al, 1999;Louie and Wilson, 2001). …”
Section: Introductionmentioning
confidence: 62%
“…There is now strong evidence that hippocampal representations active during awake states are replayed during subsequent sleep states [94,139,161,206,241]. This has been taken as evidence for a hippocampal role in consolidation.…”
Section: A1 Hippocampal Representational Replaymentioning
confidence: 99%
“…For example, the information represented in the hippocampal pyramidal cells during theta really seems to be the position of the animal within a context (see above). However, the information replayed during LIA states appears to be the recently traveled routes [139,178,206]. One possibility is that what is stored in the cortical memory is a habit-based route memory [178].…”
Section: A2 Implicationsmentioning
confidence: 99%
“…Recently there has been much progress in understanding the role of theta oscillations in organizing neuronal activity in animals (O' Keefe & Dostrovsky, 1971;O'Keefe & Recce, 1993;Nádasdy et al, 1999;Huerta & Lisman, 1993;Montgomery et al, 2008). This knowledge resulted in functional theories implicating theta in memory and other cognitive processes.…”
Section: Introductionmentioning
confidence: 99%